“Problems In Learning a Foreign Language” - Abdimurodov Doston Dilmurod ugli; Xaydarova Shaxnoza Musirmon qizi (Peerian Journals Publishing, 2022)
In today's rapidly evolving globalization, the demand for young people who are fluent in foreign languages is growing day by day. This has led to an increase in interest in foreign languages among young people and the widespread popularity of learning foreign languages. However, there are cases when young students make a number of mistakes in the process of learning a foreign language, or encounter some problematic situations, and their interest in new languages quickly disappears
Keywords: Education; audio materials; vocabulary